Five-year results of a randomised controlled trial comparing cemented and cementless Oxford unicompartmental knee replacement using radiostereometric analysis - Campi, S; Kendrick, BJL; Kaptein, BL; Valstar, ER; Jackson, WFM; Dodd, CAF; Price, AJ; Murray, DW (Elsevier, 2021)
Background: Cementless fixation is an alternative to cemented unicompartmental knee replacement (UKR). The aim of this study was to determine if cementless UKR fixation is as good as cemented by comparing the five-year migration measured radiostereometric analysis (RSA) in a randomised controlled trial.